Course of Selenoprotein-Related Myopathies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
The clinical course and genotype-phenotype correlations in 41 patients aged 1-60 years with selenoprotein-related myopathy (SEPNRM) due to SEPN1 gene mutations were evaluated retrospectively in a study at The Dubowitz Neuromuscular Center, London, and other centers in the UK.